Development of the next generation of silent aerospace propulsion configurations - Long, Tobias (2023)
Distributed electric propulsion (DEP) is a promising development in the aviation industry, with the possibility of advances in efficiency, design and noise-reduction of air transport. This is in part due to the flexibility in distributing aircraft thrust across multiple, electrically powered propellers across the aircraft. Knowledge of the airflow generated by different distributed propeller layouts is important for analysis and hence the optimisation of propeller layout to minimise the noise generated by these aircraft. In this thesis, a novel data transform originating from the image processing space, the Radon-CDT, is investigated and evaluated as a potential method to be applied in a reduced-order modelling framework for accurate and efficient calculation of flows for DEP configurations.